(untitled) (Research, Society and Development, 2024)
Objective: to assess the profile of healthcare-associated infections in pediatric patients from a Brazilian university hospital after the COVID-19 pandemic, aiming to identify epidemiological patterns and provide insights to improve prevention and control strategies. Methodology: this is a retrospective cross-sectional study, analyzing data from pediatric patients hospitalized between January 2022 and December 2023. Information was obtained from electronic medical records, including age, gender, comorbidities, length of stay, and the use of invasive devices. The sample consisted of patients aged 0 to 12 years, whose data were analyzed using descriptive statistics and significance tests. Results: a total of 69 patients were analyzed, 57.1% of whom were male. There were 7 co-infected patients, totaling 76 cases. The most prevalent age group was under 1 year (36.2%). Invasive devices included peripheral central insertion catheters (27.3%) and orotracheal tubes (27.3%). The median length of hospital stay was 24 days. The most common were surgical site infections (40.7%), followed by primary bloodstream infections (14.47%) and pneumonias (13.16%). The most prevalent microorganisms were Escherichia coli (15%) and Enterococcus sp. (15%). Of the positive cultures, 50% were gram-negative, and 37.5% showed resistance profiles. Conclusion: the study highlights the importance of continuous infection control practices, emphasizing the impact of invasive devices and the prevalence of multidrug-resistant pathogens in the pediatric environment.